The Role of Work Discipline and Work Environment on Police Job Satisfaction at the East Java Regional Police - Rahmadsyah Lubis; Slamet Riyadi (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2026)
Job satisfaction is an important factor in improving the performance and professionalism of law enforcement officials. In the context of the Indonesian National Police, work discipline and the work environment are considered key determinants that influence personnel job satisfaction. However, empirical evidence examining the relationship between these variables at the regional police level remains limited. This study aims to analyse the effect of work discipline and work environment on the job satisfaction of Indonesian National Police personnel in the East Java Regional Police. This research employs a quantitative approach using multiple linear regression analysis. The sample consisted of 267 personnel selected through random sampling. Data were collected using a structured questionnaire based on a five-point Likert scale. The analysis included validity and reliability tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity), t-tests to examine partial effects, F-tests to assess simultaneous effects, and the coefficient of determination to measure the contribution of the independent variables to the dependent variable. The findings indicate that work discipline has a positive and significant effect on job satisfaction. The work environment also demonstrates a positive and significant influence on job satisfaction. Simultaneously, both variables significantly contribute to enhancing personnel job satisfaction. These results suggest that work discipline and the work environment represent strategic factors in improving the job satisfaction of police personnel, and strengthening these aspects can support the achievement of more effective and optimal organisational performance.